Cap-independent translation of plant viral RNAs - Pettit Kneller, Elizabeth L. (2005)
The RNAs of many plant viruses lack a 5′ cap and must be translated by a cap-independent mechanism. Here, we discuss the remarkably diverse cap-independent translation elements that have been identified in members of the Potyviridae, Luteoviridae, and Tombusviridae families, and genus Tobamovirus. Many other plant viruses have uncapped RNAs but their translation control elements are uncharacterized. Cap-independent translation elements of plant viruses differ strikingly from those of animal viruses: they are smaller (<200 nt), some are located in the 3′ untranslated region, some require ribosome scanning from the 5′ end of the mRNA, and the 5′ UTR elements are much less structured than those of animal viruses. We discuss how these elements may interact with host translation factors, and speculate on their mechanism of action and their roles in the virus replication cycle. Much remains to be learned about how these elements enable plant viruses to usurp the host translational machinery.